Artificial Intelligence (AI) in English Learning: Advantages, Challenges, and Future Opportunities - Huda, Moh. Choirul; Roistika, Nia (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
This study explores the transformative role of Artificial Intelligence (AI) in English learning, examining its advantages, challenges, and future opportunities. Through a systematic literature review (SLR) of 20 studies published between 2020 and 2024, the findings reveal that AI tools such as chatbots, grammar checkers, and speech recognition systems have significantly enhanced language acquisition by enabling personalized learning, immediate feedback, and engaging educational experiences. However, challenges persist, including limited accessibility in underdeveloped regions, cultural biases in AI systems, and ethical concerns about data privacy. Moreover, the lack of teacher training and disparities in AI adoption further hinder its effectiveness. This study highlights future opportunities such as hybrid learning models and immersive technologies like Virtual Reality (VR) and Augmented Reality (AR), which offer authentic simulations for language practice. By addressing these challenges and leveraging opportunities, AI can revolutionize English learning globally, making it more inclusive, accessible, and effective for learners of diverse backgrounds.